FACTORS AFFECTING THE LEVEL OF LABOR FORCE PARTICIPATION (TPAK) OF DISTRICT/CITY WOMEN IN BALI PROVINCE - Ni Luh Wayan Sundariati; Made Heny Urmila Dewi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the effect of investment, education, MSE, and household consumption expenditure simultaneously and partially on the Female Labor Force Participation Rate (TPAK) in regencies/cities in Bali Province. The data used is secondary data on 9 districts/cities in Bali Province obtained from the Bali Provincial Statistics Agency from 2017 to 2022 (6 years). This study combines time series and cross section data (panel data) with a total of 54 observation points. This research is an associative quantitative research. The data collection method of this research is the non-behavioral observation method.This research uses an associative explanation approach. The data analysis technique used in this research is multiple linear regression analysis. The results showed that simultaneously investment, education, MSE, and household consumption expenditure had a significant effect on the TPAK of women in districts/cities in Bali Province. Partially, investment, education, MSE, and household consumption expenditure have a positive and significant effect on the TPAK of women in regencies/cities in Bali Province.